Improve the Learning Motivation of Equality Package B Students Through the Design of an Attractive and Interactive Learning Message - Hafif Assulamy; Fitri Sulistiyaningrum; Dwi Ria Ibti Disma; Warneri; Eny Enawaty (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2024)
This study analyzes the impact of exciting and interactive learning message design on the learning motivation of equality package B students at the Pontianak SKB SPNF. Using a qualitative approach to case studies, data is collected through interviews, observations, and document analysis. The results showed that conventional learning methods were less effective, while students wanted more dynamic learning. Observations identify the limitations of learning media use. Document analysis highlights the need for a learning design focusing more on student characteristics. Implications and recommendations are discussed to improve student learning quality and motivation.